Vogue : the editor's eye - MacSweeney, Eve; Bowles, Hamish (New York : Abrams, 2012)
"Vogue: The Editor's Eye celebrates the pivotal role the fashion editor has played in shaping America's sense of style since the magazine's launch 120 years ago. Drawing on Vogue's exceptional archive, this book focuses on the work of eight of the magazine's legendary fashion editors (including Polly Mellen, Babs Simpson, and Grace Coddington) who collaborated with photographers, stylists, and designers to create the images that have had an indelible impact on the fashion world and beyond. Featuring the work of world-renowned photographers such as Richard Avedon, Irving Penn, and Annie Leibovitz and model/muses, including Marilyn Monroe, Verushka, and Linda Evangelista, The Editor's Eye is a lavishly illustrated look at the visionary editors whose works continue to reverberate in the culture today"--
Introduction -- Babs Simpson -- Polly Allen Mellen -- Jade Hobson -- Carlyne Cerf de Dudzeele -- Grace Coddington -- Tonne Goodman -- Phyllis Posnick -- Camilla Nickerson.
boek
Keywords: Modeontwerpers; Mode -- Verenigde Staten -- 20ste eeuw; Mode -- Verenigde Staten -- 2000-